2002
DOI: 10.1364/ol.27.001717
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-selective switching in holographically formed polymer dispersed liquid crystals

Abstract: We have developed an optical stack of holographically formed polymer dispersed liquid-crystal (H-PDLC) devices that is fully operational with nonpolarized light sources. The device consists of two H-PDLC transmission gratings separated by a passive polarization rotator that can output a diffracted s-polarized, p-polarized, or s- and p-polarized beam simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Then, the weak measured diffraction efficiency suggest that the liquid crystal concentration is nearly homogeneous on the sample surface. Crawford and Sutherland [2,4] reported diffraction efficiency as large as 90% in Bragg setup. Such a diffraction efficiency can only be reached if the refractive index contrast between liquid crystal and polymer domains is high, which implies that the diffusion length of the liquid crystal molecules is comparable to the grating step.…”
Section: Gratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the weak measured diffraction efficiency suggest that the liquid crystal concentration is nearly homogeneous on the sample surface. Crawford and Sutherland [2,4] reported diffraction efficiency as large as 90% in Bragg setup. Such a diffraction efficiency can only be reached if the refractive index contrast between liquid crystal and polymer domains is high, which implies that the diffusion length of the liquid crystal molecules is comparable to the grating step.…”
Section: Gratingsmentioning
confidence: 99%
“…Some papers [1][2][3][4][5] have shown that PDLC with submicrometer sized droplets could be recorded using liquid crystal of the BL series (MERCK) and acrylate monomer. It has been shown in a previous paper [6] that PDLC of micrometer sized droplets could be realized also with thiol-ene monomer and liquid crystal of the BL serie.…”
Section: Introductionmentioning
confidence: 99%
“…The switching voltages tend to be much larger than those observed for bulk liquid crystals (liquid crystal displays can be driven to saturation at <5 volts) since the liquid crystal is highly constricted in holographically formed planes with dimensions of ∼ 170-200 nm for visible reflections; however, the switching times can be very attractive (in some cases < 100 µs). H-PDLCs may also be made as transmission diffraction gratings [Boiko et al (2002)] and will be discussed in greater detail in further chapters.…”
Section: Holographically Formed Polymer Dispersed Liquid Crystals (H-mentioning
confidence: 99%
“…However, in some HPDLC mixtures,12 a special alignment condition occurs where the nematic LC molecules align parallel to the grating vector to create a highly anisotropic refractive index modulation. If the refractive index of the polymer matrix is matched to the ordinary index of the LC, diffraction of s‐polarized light is very low ( n 1 S ≈ 0), while strong diffraction occurs for p‐polarized light due to the high index difference between the polymer matrix and the extraordinary index of the LC ( n 1 P ≥ 0.05 has been observed13). In comparison to previously mentioned diffractive design in isotropic materials, this approach has at least two key advantages: first, the polarizing operation of the hologram does not depend critically on high index modulation materials (since s‐polarization is suppressed by a low n 1 S regardless of the magnitude of n 1 P ); second, the polarization contrast ( η P / η S ) is not nearly as sensitive to variations in the hologram thickness.…”
Section: Holographic Lightguides Using Bragg Phase Gratingsmentioning
confidence: 99%